Semantic Anchoring with Model Transformations - Chen, Kai; Sztipanovits, Janos; Abdelwahed, Sherif; Jackson, Ethan (Model Driven Architecture - Foundations and Applications, 2005)
Model-Integrated Computing (MIC) is an approach to Model-Driven Architecture (MDA), which has been developed primarily for embedded systems. MIC places strong emphasis on the use of domain-specific modeling languages (DSML-s) and model transformations. A metamodeling process facilitated by the Generic Modeling Environment (GME) tool suite enables the rapid and inexpensive development of DSML-s. However, the specification of semantics for DSML-s is still a hard problem. In order to simplify the DSML semantics, this paper discusses semantic anchoring, which is based on the transformational specification of semantics. Using a mathematical model, Abstract State Machine (ASM), as a common semantic framework, we have developed formal operational semantics for a set of basic models of computations, called semantic units. Semantic anchoring of DSML-s means the specification of model transformations between DSML-s (or aspects of complex DSML-s) and selected semantic units. The paper describes the semantic anchoring process using the meta-programmable MIC tool suite.